Fate mapping of single NK cells identifies a type 1 innate lymphoid-like lineage that bridges innate and adaptive recognition of viral infection - Flommersfeld, Sophie; Bottcher, Jan P.; Ersching, Jonatan; Flossdorf, Michael; Meiser, Philippa; Pachmayr, Ludwig O.; Leube, Justin; Hensel, Inge; Jarosch, Sebastian; Zhang, Qin; Chaudhry, M. Zeeshan; Andrae, Immanuel; et al. (Immunity, 2021)
Upon viral infection, natural killer (NK) cells expressing certain germline-encoded receptors are selected, expanded, and maintained in an adaptive-like manner. Currently, these are thought to differentiate along a common pathway. However, by fate mapping of single NK cells upon murine cytomegalovirus (MCMV) infection, we identified two distinct NK cell lineages that contributed to adaptive-like responses. One was equivalent to conventional NK (cNK) cells while the other was transcriptionally similar to type 1 innate lymphoid cells (ILC1s). ILC1-like NK cells showed splenic residency and strong cytokine production but also recognized and killed MCMV-infected cells, guided by activating receptor Ly49H. Moreover, they induced clustering of conventional type 1 dendritic cells and facilitated antigen-specific T cell priming early during MCMV infection, which depended on Ly49H and the NK cell-intrinsic expression of transcription factor Batf3. Thereby, ILC1-like NK cells bridge innate and adaptive viral recognition and unite critical features of cNK cells and ILC1s.
CRIS-Team Scopus Importer:2023-03-23
Keywords: adaptive-like NK cell responses; ILC1; ILC1-like NK cells; MCMV; NK cells; single-cell fate mapping